(NaKUSTIKA OKEANSKOJ SREDY (B/s - (NmALXCEW(B, (Nn(B.(Ne(B.s; (NaWILOW(B, (Nk(B.(Nw(B.s; (NbREHOWSKIH(B, (NlEONID mAKSIMOWI^s; (NaNDREEWA(B, (Ni(B.(Nb(B.s; (NkOMISSIQ PO PROBLEMAM mIROWOGO OKEANA an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE GLAWs
(NaWT(B. (NUKAZANY W SODERV(B.s
Keywords: (NmORQ (B- (NaKUSTIKAs